A Prospective Study of Socioeconomic Status, Prostate Cancer Screening and Incidence Among Men at High Risk for Prostate Cancer - Rundle, Andrew (2012)
PURPOSE: Higher socio-economic status (SES) men are at higher risk of prostate cancer (PCa) diagnosis, an association commonly interpreted as a function of higher rates of prostate screening among higher-SES men. However, the extent to which screening explains this association has not been well quantified. METHODS: Within a Detroit-area cohort of 6,692 men followed up after a benign prostate procedure, a case-control study was conducted of 494 PCa cases and controls matched on age, race, duration of follow-up, and date of initial benign finding. 2000 Census data were used in a principal component analysis to derive a single factor, labeled the Neighborhood SES Index (NSESI), representing zip code-level SES. RESULTS: Among cases, higher SES was associated with a younger age at initial biopsy: −1.48 years (95% CI, −2.32, −0.64) per unit NSESI. After adjustment for confounders and duration of follow-up, higher SES was associated with more PSA tests and DRE during follow-up; 9% (95% CI, 2, 16) and 8% (95% CI, 1, 15) more respectively, per unit NSESI. Higher SES was associated with a higher risk of PCa diagnosis during follow-up, multivariable adjusted OR = 1.26 per unit increase in NSESI (95% CI, 1.04, 1.49). Further adjustment for screening frequency somewhat reduced the association between SES and PCa risk (OR = 1.19 per unit NSESI, 95% CI, 0.98, 1.44). CONCLUSIONS: Differences in screening frequency only partially explained the association between higher zip code SES and PCa risk; other health care related factors should also be considered as explanatory factors.